Internal Residual Stress Measurements in a Bioactive Glass-Ceramic Using Vickers Indentation - Peitl, Oscar; Serbena, Francisco C.; Mastelaro, Valmor R. [UNESP]; Zanotto, Edgar D. (Wiley-Blackwell, 2010)
The residual stress distribution that arises in the glass matrix during cooling of a partially crystallized 17.2Na(2)O-32.1CaO-48.1SiO(2)-2.5P(2)O(5) (mol%) bioactive glass-ceramic was measured using the Vickers indentation method proposed by Zeng and Rowcliffe (ZR). The magnitude of the determined residual stress at the crystal/glass boundary was 1/4-1/3 of the values measured using X-ray diffraction (within the crystals) and calculated using Selsing's model. A correction for the crack geometry factor, assuming a semi-elliptical shape, is proposed and then good agreement between experimental and theoretical values is found. Thus, if the actual crack geometry is taken into account, the indentation technique of ZR can be successfully used. In addition, a numerical model for the calculation of residual stresses that takes into account the hemispherical shape of the crystalline precipitates at a free surface was developed. The result is that near the sample surface, the radial component of the residual stress is increased by 70% in comparison with the residual stress calculated by Selsing's model.